The Disclosure of Carbon Emission in Indonesia: A Systematic Literature Review - Emy Dwi Nursulistyo; Y Anni Aryani; Bandi Bandi (Jurnal Dinamika Akuntansi dan Bisnis, 2023)
This study aims to provide a systematic review of research on carbon emission disclosures in the context of Indonesia. Thirty articles published in Indonesian Journals indexed by Science and Technology Index (SINTA) were selected using mapping approach (charting the field). The review found that 87% of the studies employing secondary data based quantitative method, while the other 10% studies used survey method. The resarch findings also revealed two group of determinants of carbon emission disclosure in Indonesia. 53% of the reviewed articles tested the impact of non-financial variables, for example firm age, type of industry. Meanwhile, 47% of the studies investigated the influence of financial variables (for example, leverage, firm value, and profitability) for the carbon emission disclosure. The results of this study provide an updated evaluation of prior studies and research agend for further research in carbon emission.